2012
DOI: 10.1143/jjap.51.09ld11
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Reflow on the Output Characteristics of Piezoelectric Microelectromechanical System Devices

Abstract: An animal health monitoring system and a wireless sensor node aimed at preventing the spread of animal-transmitted diseases and improving pastoral efficiency which are especially suitable for chickens, were developed. The sensor node uses a piezoelectric microelectromechanical system (MEMS) device and an event-driven system that is activated by the movements of a chicken. The piezoelectric MEMS device has two functions: a) it measures the activity of a chicken and b) switches the micro-control unit (MCU) of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Pb(Zr,Ti)O 3 (PZT) thin films are widely utilized to piezoelectric MEMS devices such as gyros, 1) inkjet heads, 2) RF-MEMS switches, 3) and ultrasonic transducers. 4) We have developed various kinds of piezoelectric devices including microscanners, 5,6) self-sensitive microcantilevers, 7,8) electrostatic field sensors, 9,10) accelerometers, 11,12) trigger switches for wireless sensor nodes, 13,14) and energy harvesters. 15,16) Moreover, we have utilized MEMS-based piezoelectric microcantilevers to investigate the crystal structure 17,18) and fatigue behavior 19) of PZT thin films.…”
Section: Introductionmentioning
confidence: 99%
“…Pb(Zr,Ti)O 3 (PZT) thin films are widely utilized to piezoelectric MEMS devices such as gyros, 1) inkjet heads, 2) RF-MEMS switches, 3) and ultrasonic transducers. 4) We have developed various kinds of piezoelectric devices including microscanners, 5,6) self-sensitive microcantilevers, 7,8) electrostatic field sensors, 9,10) accelerometers, 11,12) trigger switches for wireless sensor nodes, 13,14) and energy harvesters. 15,16) Moreover, we have utilized MEMS-based piezoelectric microcantilevers to investigate the crystal structure 17,18) and fatigue behavior 19) of PZT thin films.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, as proof of our successful measurement of the activity of chickens, the PZT output voltages were about 10 mV with frequencies below 15 Hz under 0.5 m/s 2 vibration. 25,26) Therefore, we expect that the PVDF film version sensor nodes can measure the activity of chickens.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, we reported that the PZT MEMS devices poled under 250 C-18 V-5 min conditions had only slightly lower piezoelectric output voltages after the reflow process. 25) After the above thermal poling treatment, the PZT devices were reflowed to the wireless sensor nodes. We then attached the sensor nodes to more than one hundred chickens.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, porous ceramic could be poled via pulse poling technique as traditional way of poling generally produce negligible enahcement in piezoelectric properties of porous ceramic pellets 22 . Generally, conventional dc poling is applied on piezoelectric material which takes several hours for their dipole orientation 23,24 . Such procedure of dipole alignment is not e cient in case of porous ceramics as applied electric eld concentrates in less permittivity phase 25 .…”
Section: Introductionmentioning
confidence: 99%